Recognizing CEOs and Chairmen’s personality and bank performance: new insights from signature analysis - Le TDQ; Ho TH; Ngo T; Luu TB (Taylor and Francis Group on behalf of the Chinese Economic Association – UK, 2024)
This study first uses graphology to examine the signatures of the CEOs and Chairmen of 26 commercial banks in Vietnam (2007-2020) to predict their personalities following the Big Five Personality model. Such personalities are used as a key explanatory variable to explain bank performance. Our findings extend the entrenchment theory that bank profitability is positively affected by the same personality traits of separate CEOs and Chairmen. More specifically, the findings indicate a positive relationship between bank profitability and conscientious and extraverted CEOs and Chairmen. When observing bank ownership, these two categories of personality traits are more critical to listed banks. As the first attempt to investigate whether separate CEO and chairman with the same characteristics may affect bank performance, our study will add more evidence to the existing literature about the relationship between corporate governance and bank profitability.
Keywords: Board structure; CEO; chairman; bank performance; Big Five Personality Model; corporate governance